Tinjauan Bibliometrik pada Google Scholar: Tren Publikasi tentang Reforma Agraria di Indonesia - Amri, Ikhwan; Widura, Elsa; Larasati, Fauziah (Sekolah Tinggi Pertanahan Nasional, 2024)
Agrarian reform has long interested scholars from numerous fields, but its research development has not been mapped. This study uses bibliometrics to discover Indonesian agricultural reform research trends. Publish or Perish and Google Scholar database were used to acquire data. Data analysis includes data profiles and research trends, top publication, author, and cited article sources, and text mapping. Researchers found 345 documents from 1962–2024, with research trends rising after 2018. BHUMI: Jurnal Agraria dan Pertanahan has the most articles on this topic, and MN Salim contributes the most. The most-cited article is